Effects of Dipsacus asperoides Extract on Monosodium Iodoacetate–Induced Osteoarthritis in Rats Based on Gene Expression Profiling - Chun, Jin Mi; Lee, A Yeong; Nam, Jae Yong; Lim, Kyung Seob; Choe, Mu Seog; Lee, Min Young; Kim, Chul; Kim, Joong-Sun (Frontiers in Pharmacology, 2021)
The root of Dipsacus asperoides C. Y. Cheng et T. M. Ai is traditionally used as an analgesic and anti-inflammatory agent to treat pain, rheumatoid arthritis, and bone fractures. However, neither its effects on osteoarthritis (OA) nor its effects on the arthritic cartilage tissue transcriptome have not been fully investigated. In this study, we used a rat model of monosodium iodoacetate (MIA)-induced OA to investigate the therapeutic effects of a Dipsacus asperoides ethanolic extract (DAE, 200 mg/kg for 21 days). The study first assessed joint diameter, micro-CT scans, and histopathological analysis, and then conducted gene expression profiling using RNA sequencing in articular cartilage tissue. We found that DAE treatment ameliorates OA disease phenotypes; it reduced the knee joint diameter, and prevented changes in the structural and histological features of the joint, thereby showing that DAE has a protective effect against OA. Based on the results of gene expression profiling and subsequent pathway analysis, we found that several canonical pathways were linked to DAE treatment, including WNT/β-catenin signaling. Taken together, the present results suggest molecular mechanism, involving gene expression changes, by which DAE has a protective effect in a rat model of MIA-induced OA.